Analysis Of The Effectiveness Of Implementing Voluntary Disclosure Programs In Cicadas Bandung - Meilani Purwanti; Budi Luhung (Accounting and Finance Studies, 2023)
Taxpayer awareness and compliance in terms of tax payments are still low and on the other hand there are also several Indonesian assets that are outside the territory of the Unitary State of the Republic of Indonesia. The target of increasing state revenue every year causes the government to try to make new policies related to the Voluntary Disclosure Program (Tax Amnesty Volume II). The purpose of this study is to see, know and analyze the effectiveness of the implementation of the Voluntary Disclosure Program policy (Tax Amnesty Volume II) as stated in HPP Law Number 7 of 2021 at KPP Pratama Bandung Cicadas. This type of research is qualitative with a descriptive approach where the goal is to describe the situation systematically. Data analysis aims to simplify the results of data processing, making it easy to read and interpret. The data used are primary data with field study research techniques, namely interviews and documentation. The results of this study show that the effectiveness of the implementation of the Voluntary Disclosure Program (Tax Amnesty Volume II) runs well and effectively. This can be seen from the revenue that increased significantly by 130% in 2022 and the number of taxpayers who paid PPS of 807 WP, with the number of taxpayers who paid PPS effectively because considering its voluntary nature there is no target set. The Voluntary Disclosure Program (Tax Amnesty Volume II) is also based on clear legal protections so as to increase taxpayers' confidence in new regulations made by the government.